Recent studies of the ion emission from high-current PF-1000 experiments - Skladnik-Sadowska, E.; Sadowski, M.J.; Czaus, K.; Malinowski, K.; Kwiatkowski, R.; Zebrowski, J.; Karpinski, L.; Paduch, M.; Scholz, M.; Garkusha, I.E. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The paper describes diagnostics of fast ion beams emitted from a large PF-1000 facility operated at 21…27 kV, 290…480 kJ. Those beams were measured with pinhole cameras and PM-355 nuclear track detectors, placed at different angles to the discharge axis. The measurements showed a complex spatial structure of the fast ion beams. Measurements behind an axial channel in the inner electrode have shown that some ion beams are emitted also in the upstream direction. The ion energy spectra were measured with a miniature Thomson-type spectrometer. Time-resolved measurements of ions were performed with miniature scintillation detectors placed behind a pinhole.